Phenology of European Hornet, Vespa crabro L. and Saxon Wasps, Dolichovespula saxonica Fabr. (Hymenoptera: Vespidae) and the Influence of the Weather on the Reproductive Success of Wasps Societies in Urban Conditions - Jerzy Nadolski (Universidade Estadual de Feira de Santana, 2014)
In subsequent years, changes in the period of colonies activity for both species of wasps were observed as well as the longer period of development of wasp societies in the city than in the forest. There was not found a clear influence of weather conditions in winter on date of colonies initiation. However, low temperatures and rainfall in May caused delaying the initiation of nesting. The temperature in winter had a little impact on the number of queens that survived the winter and established their colonies in spring, but the humidity in winter had influence on the count of queens and thereby on the number of future nests especially in the forest area.